2022
DOI: 10.31344/ijhhs.v6i2.438
|View full text |Cite
|
Sign up to set email alerts
|

Experiential Learning in Clinical Education Guided by the Kolb’s Experiential Learning Theory

Abstract: In clinical education, experiential learning can be an important component of the instructional process. We know that in medical college hospitals, learning that takes place at patient’s bed side or in wards is totally different from learning that takes place in the classroom. Each patient encounter is a new learning experience where new information is internalized and applied in the context of previous knowledge and experience. This emphasizes the importance of experiential learning where medical students sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 0 publications
1
11
0
Order By: Relevance
“…It is crucial to note that nursing students who need clinical practice experience exhibit limitations in understanding nursing ethics despite receiving coursework on nursing ethics in fundamental nursing courses (Huynh & He, 2018). Practical experience in clinical settings plays a crucial role in internalizing and applying knowledge (Nurunnabi et al, 2022). The results of this study align with previous findings that practical experience in clinical environments allows students to confront ethical nursing situations directly, face conflicting values, and experience the pressure of ethical decisionmaking.…”
Section: Discussionsupporting
confidence: 81%
“…It is crucial to note that nursing students who need clinical practice experience exhibit limitations in understanding nursing ethics despite receiving coursework on nursing ethics in fundamental nursing courses (Huynh & He, 2018). Practical experience in clinical settings plays a crucial role in internalizing and applying knowledge (Nurunnabi et al, 2022). The results of this study align with previous findings that practical experience in clinical environments allows students to confront ethical nursing situations directly, face conflicting values, and experience the pressure of ethical decisionmaking.…”
Section: Discussionsupporting
confidence: 81%
“…Our sample scored better than hospital nursing staff, using a similar fall-knowledge test, where almost 60% had an inadequate level of knowledge (scores of 16 or less out of 33 points) [ 47 ]. Additionally, our findings indicate that LTCF staff members’ increasing years of clinical experience caring for older people increased their knowledge of falls; i.e., that practical clinical experience can increase knowledge [ 48 ]. Previous studies examining staff knowledge of fall prevention among older people in other settings also found that staff knowledge was affected by practical experience [ 21 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Kolb’s experiential learning model (ELM) is a learner-centered model that is widely used in clinical education [ 8 ]. In this model, active learners acquire and process knowledge according to their own individual needs.…”
Section: Introductionmentioning
confidence: 99%
“…The process of learning is perceived as a continuously diverging and deepening process, during which knowledge is built on experience gained at four stages of the learning cycle (see Fig. 1 ) [ 8 ]. As a result, the knowledge they acquire is more meaningful and likely to be retained for a longer period of time.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation